Differences in BADL, IADL and Cognitive Status in a Costa Rican Sample of older adults - Johnson, David K. (2011)
Conference Series on Aging in the America: United States and Mexico, 5 de julio 2012 Asociado a Proyecto 723-B3-339 (FUNDEVI # 2791-01). Edad, Fase 1: envejecimiento saludable en zonas urbanas y rurales. (EDAD, Phase 1: Healthy Aging in Urban and Rural Areas. EDAD "The Epidemiology and Development of Alzheimer´s Disease)". NIH –Fogarty Grant Number: 1R21TW009665 – 01. Fogarty International Center (FIC), National Institute of Health (NIH). Universidad de Kansas-Universidad de Costa Rica